The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1302/0301-620x.85b5.13746
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of Simplex-tobramycin bone cement

Abstract: We prospectively investigated a consecutive series of ten patients undergoing a cemented primary total hip replacement (THR) for osteoarthritis in order to establish the elution characteristics of Simplex-tobramycin bone cement (Howmedica, Limerick, Ireland). Specimens of blood, urine and drainage fluid were collected for 72 hours postoperatively. Very high concentrations of tobramycin were found in the drainage fluid, with mean levels at one hour of 103 mg/l, which steadily declined to 15.1 mg/l after 48 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
57
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 8 publications
7
57
0
2
Order By: Relevance
“…About the use and characteristics of the Simplex P with tobramycin cement, much research has already been performed and published, and its use is widely accepted in clinical practice. 1,5,8,28 The results of this type of cement in this study were comparable to the results previously reported by Nijhof et al, using the same experimental infection model. 1 Although two tobra rabbits did have a positive culture of a bone sample distal from the cement, it showed to be effective in the prevention of infection in the majority of the cases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…About the use and characteristics of the Simplex P with tobramycin cement, much research has already been performed and published, and its use is widely accepted in clinical practice. 1,5,8,28 The results of this type of cement in this study were comparable to the results previously reported by Nijhof et al, using the same experimental infection model. 1 Although two tobra rabbits did have a positive culture of a bone sample distal from the cement, it showed to be effective in the prevention of infection in the majority of the cases.…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3] Using cement as the carrier for antibiotics provides a way to deliver high levels of antibiotics locally, without increased risk of renal toxicity or ototoxicity due to high serum levels. [4][5][6][7][8] Therefore, many orthopedic surgeons currently use either commercially available or hand-mixed antibiotic-containing bone cement in primary and revision hip and knee arthroplasties.…”
mentioning
confidence: 99%
“…As chitosan is also used as a carrier for drug delivery, we hypothesized that chitosan added to bone cement could act as a drug-delivery carrier for gentamicin. Moreover, although the exact mechanism by which antibiotics are released from PMMA cement is unknown, it has been suggested that surface elution and diffu- sion are the main mechanisms of antibiotic release from the loaded material (Sterling et al 2003, Bertazzoni et al 2004. Thus, if the porosity of cement could be increased as a result of chitosan degradation giving a more efficacious route of antibiotic release, the degree of gentamicin release would be enhanced-thereby preventing bacterial colonization and biofilm formation on the surface of bone cement.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of tobramycin cement in primary total hip replacements have been studied [21], however the pharmacokinetics of tobramycin cement in primary total knee replacements, to our knowledge, have not been reported, and thus provided the motivation for our study. This is in contrast to the standard use of systemic intravenous prophylactic antibiotics routinely used in joint replacement surgery [4].…”
Section: Introductionmentioning
confidence: 99%